Can ESG-Responsible Investing Attract Sovereign Wealth Funds’ Investments? Evidence From Chinese Listed Firms - Chen, Guifu; Wei, Boyu; Dai, Liyan (Frontiers in Environmental Science, 2022)
Global sustainable development focuses on environmental, social, and corporate governance (ESG) responsible investment as a leading-edge topic in global asset management. Because of the long-term financial returns and positive social benefits of ESG-responsible investment, ESG factors have been introduced into the investment decision-making and risk management of Sovereign Wealth Funds (SWFs). Therefore, this study examines the effect of firms’ ESG-responsible investments on the investment scale of SWFs. We also examine the different influences of ESG factors in attracting SWFs’ investment, which is of some significance in discussing the investment preferences of SWFs. We find that ESG performance attracts SWFs’ investment by increasing ROA and reducing risk. The relationship between ESG and SWFs’ investments may help managers adopt appropriate strategies to attract SWFs investments and achieve coordinated development.